Characterisation of cardiac remodeling associated with pregnancy: providing insights to peripartum cardiomyopathy - Kodogo, Vitaris (Department of Medicine, 2022)
Introduction: Maternal cardiovascular changes that occur in pregnant women are usually well tolerated by most women experiencing an uncomplicated pregnancy and are reversable postpartum. However, pregnancy can induce adverse cardiac events in previously healthy women without any known cardiovascular disease. Understanding of the maternal cardiovascular adaptation during healthy pregnancy is important to identify deviations from regular patterns caused by pathological conditions. The main objective of this study was to explore the functional, structural and molecular cardiovascular changes that are involved in healthy pregnancy with the goal to delineate possible mechanisms involved in the lack of reverse cardiovascular remodeling observed in peripartum cardiomyopathy (PPCM). Methods: Cardiovascular functional, morphological and molecular changes during pregnancy and postpartum were assessed in pregnant wild type mice (C57/BL6) and healthy women. An invitro model of cardiac hypertrophy was then used to explore the involvement of pregnancy hormones in the regulation of cardiac hypertrophy. Finally, we assessed the circulatory level of growth differentiation 15 (GDF-15) in PPCM patients and matched healthy controls. Results: Cardiac structural, functional and morphological changes were observed in mice and all the parameters were resolved postpartum. Strikingly, volume load, cardiac hypertrophy and fibrosis were sustained for a longer period postpartum than previously reported. Proteomics profiling confirmed the prolongation of cardiac hypertrophy in the postpartum and the involvement of the ubiquitin proteasome system (UPS) in the reverse remodeling of cardiac changes that occur during pregnancy. We also identified a set of transcription factors that regulates the protein expression in the postpartum. Left ventricular systolic function was significantly reduced in late pregnancy in humans. Finally, the serum level of GDF-15 was significantly lower in PPCM patients compared to healthy controls Conclusion: We conclude that pregnancy induces cardiac stress which is sustained in the postpartum period. The heart remodels and adapts to meet the demand by both the mother and the fetus. Cardiac changes that occur during pregnancy are strictly regulated and reversed postpartum. However, the postpartum period is a period of intense cardiac stress and activity which requires monitoring for any deviation that may lead to pathological conditions.